Functional and prognostic implications of left ventricular contractile reserve in patients with asymptomatic severe mitral regurgitation. Issue 11 (17th October 2005) - Lee, R; Haluska, B; Leung, D Y; Case, C; Mundy, J; Marwick, T H
Abstract : Objective: To evaluate contractile reserve (CR) determined by exercise echocardiography in predicting clinical outcome and left ventricular (LV) function in asymptomatic severe mitral regurgitation (MR). Design: Cohort study. Setting: Regional cardiac centre. Patients and outcome measures: LV volumes and ejection fraction (EF) were measured at rest and after stress in 71 patients with isolated MR. During follow up (mean (SD) 3 (1) years), EF and functional capacity were serially assessed and cardiac events (cardiac death, heart failure, and new atrial fibrillation) were documented. Results: CR was present in 45 patients (CR+) and absent in 26 patients (CR−). Age, resting LV dimensions, EF, and MR severity were similar in both groups. Mitral surgery was performed in 19 of 45 (42%) CR+ patients and 22 of 26 (85%) CR− patients. In patients undergoing surgery, CR was an independent predictor of follow up EF (p  =  0.006) and postoperative LV dysfunction (EF < 50%) persisted in five patients, all in the CR− group. Event-free survival was lower in surgically treated patients without CR (p  =  0.03). In medically treated patients, follow up EF was preserved in those with intact CR but progressively deteriorated in patients without CR, in whom functional capacity also deteriorated. Conclusions: Evaluation of CR by exercise echocardiography may be useful for risk stratification and may help to optimise the timing of surgery in asymptomatic severe MR.